‘Candidatus Rickettsia nicoyana’: A novel Rickettsia species isolated from Ornithodoros knoxjonesi in Costa Rica - Moreira Soto, Rolando Daniel (2017)
Rickettsiae are intracellular bacteria commonly associated with hematophagous arthropods. Most of them have been described in hard ticks, but some have been found in soft ticks. Here we report the detection and isolation of a new Rickettsia from Ornithodoros knoxjonesi larvae collected from Balantiopteryx plicata (Emballonuridae) in Nicoya, Costa Rica. Two ticks were processed to detect Rickettsia spp. genes gltA, ompA, ompB, and htrA by PCR. Part of the macerate was also inoculated into Vero E6 and C6/36 cell lines, and cells were evaluated by Giménez stain, indirect immunofluorescence assay (IFA), and PCR. Both ticks were positive by PCR and rickettsial growth was successful in Vero E6 cells. Amplification and sequencing of near full length rrs, gltA, sca4 genes, and fragments of ompA and ompB showed that the Rickettsia sp. was different from described species. The highest homologies were with ‘Candidatus Rickettsia wissemanii’ and Rickettsia peacockii: 99.70% (1321/1325) with both sequences for rrs, 99.58% (1172/1177) and 99.76% (1246/1249) for gltA, 99.26% with both sequences (2948/2970 and 2957/2979) for sca4, 98.78% (485/491) and 98.39% (2069/2115) for ompA, and 98.58 (1453/1474) and 98.92% (1459/1475) for ompB; respectively. Bat blood, spleen, liver, and lung samples analyzed for Rickettsia detection were negative. Results demonstrate that the Rickettsia isolated from O. knoxjonesi is probably an undescribed species that belongs to the spotted fever group, for which ‘Candidatus Rickettsia nicoyana’ is proposed. Considering that B. plicata inhabits areas where contact with humans may occur and that human parasitism by Ornithodoros has been reported in the country, it will be important to continue with the characterization of this species and its pathogenic potential.